Gambaran Kecemasan Korban setelah Mengalami Bencana Banjir - Najwa Chairunnisa Fauzi; Endang Setyaningsih (Jurnal Ilmu Sosial dan Humaniora, 2026)
Flooding is a natural disaster that causes not only physical damage, material loss, and the disruption of community activities but also impacts the psychological well-being of victims, specifically by inducing anxiety. Post-disaster anxiety can affect an individual's ability to carry out daily activities and adapt to the post-disaster environment. This study aims to describe the anxiety experienced by flood victims in Pidie Jaya Regency in 2025. A qualitative, descriptive approach was employed. Three flood victims served as informants, selected using purposive sampling. Data were collected through semi-structured interviews and analyzed using the Miles, Huberman, and Saldaña interactive model. The results indicate that all informants continued to experience anxiety, characterized by physiological symptoms (sleep disturbances, heart palpitations, and physical tension), cognitive symptoms (recurring thoughts about the possibility of recurring floods), emotional symptoms (fear, anxiety, and worry), and behavioral changes (increased vigilance and preparedness). This anxiety was influenced by traumatic experiences, flood-related losses, and concerns regarding the safety of family members. These findings suggest that post-disaster recovery efforts must address mental health through psychosocial support, preparedness education, and psychological counseling, enabling victims to adapt and build resilience against potential future disasters.